The Influence of Financial Anxiety, Financial Literacy, and Financial Digitalization on the Financial Stability of MSMEs in Mataram City - Lalu Fahril Dwi Suryadi; Burhanudin (LP2M IAIN Palopo, 2026)
The financial stability of MSMEs in Mataram City is threatened by financial anxiety, low financial literacy, and suboptimal digitalization, with MSMEs dominating 10,471 micro-business units vulnerable to economic fluctuations. This study aims to examine the effect of financial anxiety, financial literacy, and financial digitalization on the financial stability of MSME actors. Using a causal quantitative design with PLS-SEM, the population of all MSMEs in Mataram (10,471 units), a sample of 120 purposive respondents, a 5-point Likert questionnaire instrument, and SmartPLS 4.0 analysis. The results show that financial literacy has a significant positive effect (coefficient 0.642, p = 0.000), financial anxiety has a significant positive effect (0.157, p = 0.030), while digitalization is insignificant (0.057, p = 0.461), with an R-square of 0.598. The conclusion recommends financial literacy training for the Cooperative Office to increase MSME resilience.